Correlations of Cancer-Related Fatigue with Clinicopathological Features and Quality of Life in Gastric Cancer - Dong Liu; A-Dong Xia; Yue-Long Xing; Kai Zhang; Dan Chen (Gastroenterology Research and Practice)
Objective. To explore the correlations of cancer-related fatigue (CRF) with clinicopathological features and quality of life in gastric cancer. Methods. Using a convenient sampling method, 230 patients with gastric cancer admitted to our hospital from March 2020 to July 2022 were collected. They were divided into the fatigue group (n=152) and the nonfatigue group (n=78) according to the presence/absence of CRF. Relevant data were collected and compared. Results. Statistically significant differences were found between the two groups in age ratio (χ2=41.671, P<0.001), T stage ratio (χ2=9.973, P=0.019), N stage ratio (P<0.001), PS score (P<0.001), and the degree of gastric cancer thickening (14.21±3.32 vs. 12.12±3.81 mm, t=4.572, P<0.001). Patients with gastric cancer had the lowest CRF Brief Fatigue Inventory (BFI) score for general activities (2.26±0.37) and high scores for work activities (6.23±0.24) and enjoyment of life (7.11±1.34). Pearson’s correlation analysis revealed a positive correlation between patient emotions and the CRF BFI score (r=0.443, P=0.001). Patients with mild, moderate, and severe CRF showed statistically significant differences in physical functioning (83.34±21.12 vs. 65.23±21.14 vs. 32.25±17.29, F=15.382, P<0.001), role emotional (72.53±21.21 vs. 67.33±27.56 vs. 54.37±26.45, F=14.483, P<0.001), fatigue (49.12±18.44 vs. 54.61±26.64 vs. 67.51±14.27, F=13.581, P<0.001), bodily pain (56.56±25.12 vs. 76.43±21.71 vs. 80.32±12.39, F=14.582, P<0.001), appetite reduction (57.45±25.47 vs. 69.51±16.21 vs. 76.23±27.58, F=14.592, P<0.001), and overall health status and quality of life (67.21±19.45 vs. 53.43±22.32 vs. 43.43±12.52, F=16.494, P<0.001). After chemotherapy, the average CRF BFI scores of the partial remission (PR), disease stability (SD), and disease progression (PD) groups all reduced than those before chemotherapy (all P<0.05). At 3 months of follow-up, a comparison of the average CRF BFI scores with those before chemotherapy revealed a decrease in the SD and PR groups and an increase in the PD group. Conclusion. In conclusion, CRF is correlated with age, T stage, and N stage in gastric cancer. The later the T and N stages, the more significant the effect on fatigue. Moreover, CRF can also affect the quality of life in gastric cancer, and the severer the CRF, the poorer the quality of life.